Analysis Of Strategies To Increase Customer Satisfaction Using Swot Analysis At Barbershop 96 In Bengkulu City Post Covid 19 (The Manager Review, 2025)
This research aims to analyze customer satisfaction at Barbershop 96 through a SWOT analysis approach, with a focus on revealing strengths, weaknesses, opportunities and threats that influence service quality. The research methods used include in-depth interviews with customers, distributing questionnaires, and direct on-site observation. The collected data is then analyzed qualitatively and described. The results of the SWOT analysis are expected to provide in-depth insight into the factors that influence customer satisfaction at Barbershop 96. Service advantages and internal weaknesses at Barbershop 96 will be identified, while opportunities and threats from Barbershop 96's external environment will also be evaluated. Next, strategy recommendations will be presented to increase customer satisfaction and optimize business performance. Interview and questionnaire methods will help explore customer perceptions and expectations in more depth, and provide data to measure satisfaction levels. Direct observation at Barbershop 96 will provide a practical understanding of service implementation and customer response in real-time. This research is expected to provide a significant contribution in understanding the factors that influence customer satisfaction in the barbershop industry, as well as providing strategic guidance for Barbershop 96 to improve its service and competitiveness in a competitive market.